Sustainability analysis of the palm sugar industry in Hulu Sungai Tengah Regency: Perspectives on local economy, public policy, and labor law‎ - Nurani, Muhammad Fahmi; Arabi, Ibnu; Anwary, Ahdie (Universitas Islam Indonesia, 2025)
IntroductionThe palm sugar industry in Hulu Sungai Tengah, South Kalimantan, is a traditional sector that supports the local economy and provides employment in the informal workforce. Despite its cultural and economic significance, the industry faces serious challenges, including unstable raw material supply, limited innovation, weak market access, and the absence of legal protection for workers. These issues raise critical questions regarding the long-term sustainability of this local industry.ObjectivesThis study aims to analyze the sustainability of the palm sugar industry in Hulu Sungai Tengah from the perspectives of local economic development, public policy, and labor law, while also integrating insights from Islamic economics and finance to propose a holistic framework for industry revitalization.MethodThis research applies a qualitative descriptive-exploratory approach involving in-depth interviews, field observations, and document analysis. The participants consist of palm sugar artisans, policymakers, small and medium enterprise representatives, and local government officials. Data were examined using a triangulation technique to ensure validity, and the Triple Bottom Line framework guided the analysis.ResultsThe findings reveal that the palm sugar industry retains strong economic potential due to naturally growing sugar palms and established cultural practices. However, systemic challenges persist, including lack of planned cultivation, reliance on traditional processing methods, weak branding, and widespread informality in labor practices. Islamic finance mechanisms such as profit-and-loss sharing, as well as instruments like zakat and waqf, offer promising pathways to strengthen capital access, innovation, and social welfare within the sector.ImplicationsThe study highlights the need for integrated policies between local government, financial institutions, and community stakeholders. Practical recommendations include cultivating sugar palms systematically, introducing innovation and digital marketing, providing fair labor protection, and mobilizing Islamic social finance. These steps can enhance resilience, competitiveness, and sustainability in line with both national development priorities and Islamic economic principles.Originality/NoveltyThis study contributes a multidisciplinary perspective by linking local economic analysis, public policy, labor law, and Islamic finance in the context of a traditional industry. It offers a novel framework for understanding how ethical and Shariah-compliant economic instruments can support the sustainable transformation of rural industries, an area that has received limited scholarly attention in South Kalimantan.